Antibacterial Activity Of Microwave Synthesized Hydroxyapatite Against Cariogenic Bacteria: A Preliminary Study - Ahmad Zharif Ibrahim; Alaa Sabah Hussein; Hasnah Begum Said Gulam Khan; Norzalina Ghazali (Elsevier, 2024)
Indexed by WOS/ Scopus